Cross-cultural differences in somatic awareness and interoceptive accuracy: a review of the literature and directions for future research - Ma-Kellams, Christine (Frontiers in Psychology, 2014)
This review examines cross-cultural differences in interoceptive processes and the role of culturally-bound epistemologies, historical traditions, and contemplative practices to assess four aspects of culture and interoception: 1) the extent to which members from Western and non-Western cultural groups exhibit differential levels of interoceptive accuracy and somatic awareness; 2) the mechanistic origins that can explain these cultural differences, 3) culturally-bound behavioral practices that have been empirically shown to affect interoception, and 4) consequences for culturally-bound psychopathologies. The following outlines the scope of the scientific review. Part 1 reviews studies on cultural variation in spontaneous somatic word use, linguistic expressions, traditional medical practices, and empirical laboratory studies to assess the evidence for cultural differences in somatic processes. Integration of these findings suggests a startling paradox: on the one hand, non-Western cultures consistently exhibit heightened somatic focus and awareness across a variety of contexts; on the other hand, non-Western cultures also exhibit less interoceptive accuracy in laboratory studies. Part 2 discusses the various mechanistic explanations that have been proposed to explain these cultural differences in somatic awareness and interoceptive accuracy, focusing on cultural schemas and epistemologies. Part 3 addresses the behavioral and contemplative practices that have been proposed as possible “interventions,” or methods of cultivating bodily awareness and perceptual accuracy. Finally, Part 4 reviews the consequences of interoceptive processes for psychopathology, including somatization, body dysmorphia, eating disorders, and anxiety disorders.